THE INFLUENCE OF SOCIO-DEMOGRAPHIC FACTORS ON JOB STRESS LEVEL IN FOREIGN-OWNED MANUFACTURING COMPANIES IN OGUN STATE, NIGERIA - Ajibade David (School of Business, IPB University (SB-IPB), 2016)
This study examined the influence of socio-demographic factors on level of job stress in foreign-owned manufacturing companies in Ogun State, Nigeria with the specific objectives of investigating level of job stress as well as the socio-demographic characteristics influencing the job stress level. This study used cross sectional analytical design with quantitative approach. Data were collected using structured questionnaire and the data collected were statistically analyzed using percentage and weighted mean; while the hypotheses formulated were tested using spearman rank correlation and multiple regressions. The results of the study showed that with the exception of gender (P<0.05; coeff r = -0.003), and employees’ department (P<0.05; coeff r = -0.003) that impacted negatively on employees stress level, other socio-demographic characteristics such as age (P<0.05: coeff r = 0.074), marital status (P<0.05; coeff r = 0.125), educational level (P<0.05; coeff r = 0.037), employees’ cadre (P<0.05; coeff r= 0.038), years of working experience (P<0.05; coeff r= 0.146), income (P<0.05; coeff r= 0.025) and employees’ position (P<0.05; coeff r= 0.103) had positive impacts on the employees’ job stress level. This concludes that socio-demographic factors exert significant influence on employees’ job stress level. It is recommended that employers should always take into consideration employees’ socio-demographic characteristics when assessing their job stress level because it can provide useful information on specific individual characteristics influencing stress level in workplace. Keywords: socio-demographic, stress, employees, cross sectional analytical, Ogun